Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1016/0014-5793(94)00548-6
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the erythrocyte glutathione redox balance by N‐acetylcysteine, captopril and exogenous glutathione

Abstract: The effect of the thiol containing compounds N-acetylcysteine and captopril on glutathione metabolism in human erythrocytes has been investigated non-invasively using 'H spin echo NMR. N-Acetylcysteine was found to increase the reduced form of glutathione while captopril increased the oxidized form, but no changes in the total glutathione concentration were observed. Incubation of the cells with buthionine sulphoximine to inhibit de novo glutathione synthesis did not affect the response. The results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Previous studies demonstrated increases in the GSH/GSSH ratio in NAC-treated erythrocytes and mucosal cells. 21,22 In this study, total GSH decreased in MG63 cells when exposed to NAC (Figure 4). Generally, cells respond to ROS by up-regulating the synthesis of antioxidants to protect cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies demonstrated increases in the GSH/GSSH ratio in NAC-treated erythrocytes and mucosal cells. 21,22 In this study, total GSH decreased in MG63 cells when exposed to NAC (Figure 4). Generally, cells respond to ROS by up-regulating the synthesis of antioxidants to protect cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 75%